Access to maternity waiting home services and its determinants among women in Ethiopia: systematic reviews and meta-analysis - Hidoto, Kassahun Tafesse; Gidebo, Kassa Daka; Koyira, Mengistu Meskele; Domínguez, Maria Luisa Guillén (Frontiers in Global Women's Health, 2024)
IntroductionGlobally, maternal mortality is a major public health problem mainly due to a lack of access to skilled care during childbirth. Maternity waiting homes (MWHs) play a critical role in accessing emergency obstetric care for pregnant women during childbirth. However, available studies show inconsistent findings about women's utilization of maternity waiting homes. Therefore, the aim of this review was to identify the pooled prevalence of women's utilization of maternity waiting homes and its associated factors in Ethiopia.MethodWe used the PRISMA guidelines to report the review. We searched for potentially eligible studies in Google Scholar, PubMed, Cochrane Library, and Google using Medical Subject Heading terms and keywords. The retrieved articles were screened and assessed for quality. The heterogeneity across studies was checked using Cochran's Q test and I2 statistics. The pooled levels of women's utilization and associated factors were analyzed using meta-analysis. The publication bias was measured using the funnel plot and Egger's test. The subgroup analysis and sensitivity analysis were carried out to identify the studies with high effects.ResultsA total of 11 eligible studies with 11,784 study participants were included. The utilization of MWHs was in the range of 7%–42.5%. The pooled estimate of women's utilization of maternity waiting homes was 22.49%. Factors associated with utilization included women's decision-making power, access to transport, walking distance to the nearest facility, and having a companion.Conclusion and recommendationThe overall prevalence of maternity waiting home utilization in Ethiopia is low, with significant variation across regions. Health sector program administrators should focus on both the consumer and healthcare system.Systematic Review RegistrationThe review protocol was registered in PROSPERO (number CRD42021243526).